Hilara regnealai Pârvu (Diptera: Empididae), new record for Turkish fauna with female description - Çiftçi, Mustafa Cemal (Acta entomologica slovenica (Ljubljana), 2007)
Hilara regnealai Pârvu, 1991 is a new species record for Turkish fauna and also the genus Hilara Meigen is recorded for the first time in Turkey. The description of the previously unknown female is given.
Keywords: dvokrilci; Empididae; entomologija; favna; Turčija; Turkey